Maritime medicine in Ukraine: the present-day state and some lines of its reforming - Gozhenko, A.I. (Актуальні проблеми транспортної медицини, 2011)
Examined the role of the Ukrainian Research Institute of Transport Medicine in the structure of marine medicine in Ukraine. A scheme for reform of maritime medicine in Ukraine based on scientific research experts from the Instituteof Transport Medicine.